2014
DOI: 10.1155/2014/285421
|View full text |Cite
|
Sign up to set email alerts
|

Activation Effects of Polysaccharides ofFlammulina velutipesMycorrhizae on the T Lymphocyte Immune Function

Abstract: Flammulina velutipes mycorrhizae have increasingly been produced with increasing of F. velutipes production. A mouse model was thus used to examine potential effect of F. velutipes mycorrhizae on the immune function. Fifty female Wistar mice (5-weeks-old) weighed 15–20 g were randomly allocated into five groups. Polysaccharide of F. velutipes mycorrhizae were treated with mice and mice spleen lymphocytes. The levels of CD3+, CD4+, and CD8+ T lymphocyte, interleukin-2 (IL-2), and tumor necrosis factor-a (TNF-α)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 20 publications
0
21
0
4
Order By: Relevance
“…Yin et al (2010) isolated polysaccharides from F. velutipes mycelium which were shown to increase nitric oxide (NO) production, IL-1 production and TNF-α production from macrophages in a dose-dependent manner. Another study showed that polysaccharides from F. velutipes mycorrhizae (PFVM) increased the body weight of mice and the weight ratio of the thymus and spleen (Yan et al, 2014). According to the study, the T cell subpopulation of thymocytes and splenocytes were modulated by the administration of PFVM; CD3 + , CD4 + and CD4 + /CD8 + counts were increased while CD8 + counts decreased in a dose dependent manner.…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…Yin et al (2010) isolated polysaccharides from F. velutipes mycelium which were shown to increase nitric oxide (NO) production, IL-1 production and TNF-α production from macrophages in a dose-dependent manner. Another study showed that polysaccharides from F. velutipes mycorrhizae (PFVM) increased the body weight of mice and the weight ratio of the thymus and spleen (Yan et al, 2014). According to the study, the T cell subpopulation of thymocytes and splenocytes were modulated by the administration of PFVM; CD3 + , CD4 + and CD4 + /CD8 + counts were increased while CD8 + counts decreased in a dose dependent manner.…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…Lee et al [45] found that the mushroom could increase the concentration of IFNγ that has a toxic function against lymphoma cell. The polysaccharides of needle mushroom were found to produce different cytokines and increase the weight of immune stimulating organs in laboratory animals [4,5]. The mushroom polysaccharides increased the body weight of experimental mice and the weight ratio of the thymus and spleen, as well as it could modulate the T cell subpopulation of thymocytes and splenocytes [30].…”
Section: Immune Functionsmentioning
confidence: 99%
“…Polysaccharides are considered to be the most activate component in mushrooms which have immune stimulating activities [3]. In addition, the polysaccharides in mushroom have been found to produce different cytokines and increase the weight of immune stimulating organs in laboratory animals [4,5]. Presently, researchers have become interested in the role of medicinal mushrooms in poultry production systems.…”
Section: Introductionmentioning
confidence: 99%
“…T cells were induced by using extractions according to previously described method (Yan, Liu, Mao, Li, & Li, 2014). Briefly, extractions were dissolved with Dimethyl Sulphoxide (DMSO) to a proper concentration for the low (LG), middle (MG), high (HG) dosages (4, 8, 16 mg/mL) (0 mg/mL as a control group, CG).…”
Section: Screening Active Extractions By Induceding T Cellmentioning
confidence: 99%